Effect of Types and Concentrations of Stabilizers on the Characteristics of Emprit Ginger (Zingiber Officinale Var. Amarum) Extract Tempe Beverage - Ahmad Farhan; Anwar Kasim; Rini B (Lembaga Penelitian dan Pengabdian, Universitas Andalas, 2023)
In the making of emprit ginger extract tempe beverage requires the addition of a stabilizer to increase the stability and viscosity of the product and each stabilizer has a different effect from one another. This study aims to determine the characteristics of gum arabic stabilizer, Carboxymethyl Cellulose (CMC) and soy lecithin in emprit ginger extract tempe beverage used 0%, 0.3%, 0.5%, 0.7%, and 0.9% of each stabilizer. The observations were physical properties such as stability and viscosity and chemical analysis includes protein content, and pH value. This study used completely randomized design (CRD) with two factors (F1 is the type of stabilizer and F2 is the concentration of the stabilizer) and carried out with 3 replications. The obtained data was analyzed with ANOVA followed by Duncan's test. Decision system analysis was performed using the MADM-SAW method to obtain the best type and concentration of stabilizer. CMC was found out in the first rank of used stabilizers in 0.5% concentration with stability in 21%, viscosity was 2.17 poise, an ash content was 0.26%, protein content was 12.77%, and pH value was 6.2.